Consciousness-Based Education - Maharaj-Sharma, Rawatee (Daily Express, 2008)
This article reflects on the ideas presented at a two-day conference on "Adding Consciousness Based Education for Total Brain Development," which was held in Trinidad. The consciousness-based education programme involves students' participation in transcendental meditation for short periods before the formal start of school and at the end of the school day. This programme is expected to strengthen the cognitive, physiological, and affective domains of learning, while promoting healthy lifestyle choices and positive behaviour
Keywords: Consciousness-based education; Transcendental meditation; Educational strategies